Production profile of lipid mediators in conjunctival lavage fluid in allergic and infectious conjunctivitis in guinea pigs - Hayashi, Akane; Kobayashi, Koji; Nakamura, Tatsuro; Nagata, Nanae; Murata, Takahisa (Frontiers in Allergy, 2023)
Introduction: Conjunctivitis is a major ocular disease classified into allergic or infectious. The pathological features of conjunctivitis are not fully understood despite its high morbidity rate; thus, its differentiation can be difficult. Materials and methods: We used ovalbumin-induced allergic conjunctivitis and lipopolysaccharide-induced infectious conjunctivitis models of guinea pigs. Both models showed conjunctival swelling. Histological studies revealed that numerous eosinophils infiltrated the conjunctiva in the allergic model, whereas neutrophils infiltrated the conjunctiva in the infectious model. We collected conjunctival lavage fluid (COLF) and comprehensively analyzed lipid production using liquid chromatography-tandem mass spectrometry. Results: COLF showed increase of 20 and 12 lipid species levels in the allergic and infectious models, respectively. Specifically, the levels of a major allergic mediator, prostaglandin D2 and its three metabolites and several cytochrome P450catalyzed lipids increased in the allergic model. In the infectious model, the levels of prostaglandin E2 and 8-iso-prostaglandin E2 increased, indicating tissue inflammation. Moreover, the level of 12-oxoeicosatetraenoic acid, a lipoxygenase metabolite, increased in the infectious model. Conclusion: These differences in lipid production in the COLF reflected the pathological features of allergic and infectious conjunctivitis.